Calculation method of cracking load and deflection of textile reinforced self-stressing concrete. (18th October 2021) - Wang, Boxin; Yuan, Ke; Lu, Xinyu; Zhao, Jianyu
Highlights: Self-stress can significantly improve the cracking resistance of TRSSC beams. FDM was used for the first time to research the bending properties of TRSSC. A model was established to calculate the cracking load and deflection of TRSSC. Abstract: Given the self-stressing property of its matrix, textile reinforced self-stressing concrete (TRSSC) has excellent cracking resistance and is especially beneficial to the tensile position of the structure in enhancing cracking resistance and stiffness. In this research, the cracking resistance of TRSSC under bending is studied through the four-point bending test. Experimental results show that the cracking load of specimens increases by 33.39% due to self-stress, and the cracking resistance of the specimens increases by 55.23% due to the increase in the number of textile layers. The calculation method for cracking load and deflection is proposed based on the basic equation of elasticity and the finite difference method. The theoretical analytical solution is consistent with the experimental value.